2018
DOI: 10.1080/07347332.2018.1499693
|View full text |Cite
|
Sign up to set email alerts
|

Low-dose computed tomography lung cancer screening as a teachable moment for smoking cessation among African American smokers: A feasibility study

Abstract: Low-dose computed tomography (LDCT) screening may be a teachable moment for smoking cessation among African Americans. African Americans have been understudied within the context of LDCT and smoking cessation. The study objective was to evaluate the feasibility of recruiting African Americans’ to a future longitudinal trial and to obtain sample size estimates for that trial. Participants (N=18) were African Americans eligible for LDCT screening who completed a questionnaire at three time points. Self-efficacy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…There is no consistent evidence of a "licence to smoke" effect, whereby a normal scan discourages quitting. Indeed, there is some research to suggest that LCS represents a "teachable moment" where participants maybe particularly receptive to smoking cessation interventions [189,[195][196][197]. Research published in abstract form from the UK has shown that quit rates of over 30% at 1 year can be achieved using opt-out, co-located, comprehensive cessation services with follow-up [183,198].…”
Section: Evidence Reviewmentioning
confidence: 99%
“…There is no consistent evidence of a "licence to smoke" effect, whereby a normal scan discourages quitting. Indeed, there is some research to suggest that LCS represents a "teachable moment" where participants maybe particularly receptive to smoking cessation interventions [189,[195][196][197]. Research published in abstract form from the UK has shown that quit rates of over 30% at 1 year can be achieved using opt-out, co-located, comprehensive cessation services with follow-up [183,198].…”
Section: Evidence Reviewmentioning
confidence: 99%